DESIGNING SERVICE BLUEPRINT AT THE HOTEL LABORATORY OF CIPUTRA UNIVERSITY - agustina, karina enny; Hermeindito (Jurnal Bisnis dan Keuangan, 2024)
The tourism industry has recovered from the effect of pandemic covid-19, that makes the stakeholders in the hospitality sector must be able to respond; including hotel managers and higher education institutions that have tourism and hospitality study programs. However, this phenomenon is inversely proportional to the number of workers in the tourism industry who have tourism education up to a bachelor’s degree. This shows that there is a need for useful learning facilities to accelerate the competency of Hospitality graduates, such as the availability of practical laboratories and hotel systems that are operated to resemble real activities. The object of this research is the Ciputra University Laboratory Hotel which operates on March 2023 with a fluctuative occupancy rate. The operational activities of the Hotel Laboratory are handled by staff (internship students) who changes every day which makes a great possibility of service inconsistencies delivered to the hotel guests, therefore it is necessary to have a service system that can be used as a reference for the services delivered to the guests hotel in a form of a service blueprint. This research uses a qualitative approach with triangulation of data sources, the number of informants are 8 people represented by experts in the field of hotel management, internal management of the Hotel Laboratory and customers (guests) of the Hotel Laboratory. The final results of this research is represented in a form of service blueprint chart that can be implemented by employees (internship students) who are working at the Hotel Laboratory of Ciputra University.